PENGARUH STRES PADA KESEHATAN JARINGAN PERIODONTAL - Ratih Larasati (Poltekkes Kemenkes Denpasar, 2017)
Stress is a psycho-physiological reactions to various stimuli emotionally or physically interfere with homeostasis, and can exacerbate diseases result from bacterial and viral infections in animals and humans. Psychological stress or psychosomatic conditions encourage the immunological changes. Namely stress hormone CRH, ACTH and glucocorticoids can affect the immune response resulting in bone loss, tissue damage, loss of attachment, and can inhibit wound healing. One of the periodontal pathogenic bacterial species is Porphyromonas gingivalis. Porphyromonas gingivalis bacteria found in dental plaque and bacteria that cause periodontal tissue pathological changes with the activation of the immune and inflammatory response of the host, and directly affects the cells of the periodontium. The high level of stress is accompanied by a lack of oral health can lead to more severe periodontal conditions. Keywords: stress, periodontal, Porphyromonas gingivalis